(untitled) (Chicago, 1970)
This book introduce about America in Vietnam: the circle of deception, Vietnam war stories, Vietnam and American elections, The President, the polls, and Vietnam, American aid is damaging Thai society, Mao and the death of the revolution.
Keywords: Chiến tranh Việt Nam, 1961-1975,Vietnam War, 1961-1975; Hoa Kỳ,United States